2021
DOI: 10.1590/1678-4499.20200449
|View full text |Cite
|
Sign up to set email alerts
|

Phenomics approaches: genetic diversity and variance components in a S2 guava family by seed traits

Abstract: Guava is of great economic importance in Brazil. The development of new cultivars by obtaining inbreeding lines has been a promising option. The objective of this work was to evaluate the S 2 families of Psidium guajava using seed attributes. Different characters of physiological quality of guava seeds were studied, in addition to performing digital phenotyping of characteristics of geometry, texture and colors of the seeds. The variables were analyzed simultaneously using the Ward-Modified Location Model (MLM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 24 publications
1
1
0
Order By: Relevance
“…The high genetic variance values resulted in high heritability (h 2 ) estimates for all variables, which ranged from 92.2, for AA, to 99.7%, for TSW. Similar h 2 results were observed for 1000-seed weight, GSI, RL, and SDW in passion fruit hybrids (Cremasco et al 2021); and for SDW, RL and TSW in seeds of S2 guava families (Silva et al 2021). The same families as in this study were evaluated by Mendes et al (2022), who reported h 2 values of 86.0 and 92.0% for AUDPCM and fruit yield, respectively.…”
Section: Genetic Parameters and Correlations Between Traitssupporting
confidence: 72%
See 1 more Smart Citation
“…The high genetic variance values resulted in high heritability (h 2 ) estimates for all variables, which ranged from 92.2, for AA, to 99.7%, for TSW. Similar h 2 results were observed for 1000-seed weight, GSI, RL, and SDW in passion fruit hybrids (Cremasco et al 2021); and for SDW, RL and TSW in seeds of S2 guava families (Silva et al 2021). The same families as in this study were evaluated by Mendes et al (2022), who reported h 2 values of 86.0 and 92.0% for AUDPCM and fruit yield, respectively.…”
Section: Genetic Parameters and Correlations Between Traitssupporting
confidence: 72%
“…Variation indices equal to or greater than unity are desirable, for having a greater chance of success in selection (Vencovsky 1987), which were identified in this study. The results of Silva et al (2021) for guava seed traits were comparable, where the high h 2 values contributed to good variation indices. SV = source of variation; df = degrees of freedom; GSI = germination speed index (%); G = germination (%); AA = accelerated aging (%); SL = shoot length (cm); RL = root length (cm); SDW = shoot dry weight (mg seedling -1 ); RDW = root dry weight (mg seedling -1 ); Area = (cm²); Dmax = maximum diameter (cm); Dmin = minimum diameter (cm); Circ.…”
Section: Genetic Parameters and Correlations Between Traitsmentioning
confidence: 73%
“…Different results were observed by Silva et al (2021), who found values of heritabilities above 90% for the variables related to seed quality in S 2 families of Psidium guajava using the Least squares method (LS).…”
Section: Genetic Parametersmentioning
confidence: 81%
“…The GroundEye ® system is an effective and promising tool to quantify genetic diversity from seed traits in an early, fast, non-destructive, and easy-to-reproduce manner (Venora et al 2007). Nonetheless, aspects related to the physiological quality of the seeds under evaluation must not be neglected, as they are important criteria for the selection of superior genotypes (Silva et al 2021). Passion fruit seeds must exhibit rapid and homogeneous germination, which allows for faster, continuous, and uniform seedling formation.…”
Section: Discussionmentioning
confidence: 99%